Performance and Emission Characteristics of Ozonated Coconut Oil in a Single-Cylinder, Direct Injection Diesel Engine - K. Dimapalao, Muhamad-Ali (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study investigated experimentally the performance and emissions characteristics of ozonated coconut oil blended with neat diesel fuel at 1, 3, 5, 7.5 and 10% by volume used as biodiesel for a naturally-aspirated four stroke, air-cooled, direct injection, single cylinder diesel engine. The experiment was conducted at four different engine loadsi a full (100%) load and three partial (25, 50 and 75%) loads at three different speeds (3600, 3270 and 2945 rpm) of the engine. Performance test results showed that the engine exhibited the highest specific fuel consumption (SFC) at lowest engine load of 25 % and lowest SFC at engine load of 75% for all the test fuels (OCO-PBDF blends and neat PBDF). SFC also decreased with speed. Comparing with the base neat diesel fuel, results showed a little decrease in the SFC at lower loads especially at lower engine speeds. Emission test results showed that carbon dioxide (COz) emissions decreased with load and speed for all blends but an exact opposite was observed for total hydrocarbon (THC) emission. Maximum carbon monoxide (CO) emission occurred at full engine load of 100 % and maximum for nitrogen oxides (NOx) at 75 % load and minimum at 25 % load. Furthermore, in comparison with the neat diesel fuel, blended fuels decreased in CO emission especially at lower engine loads but an increase in NOx and THC emission for almost all the test engine loads and speeds.